Strnišev lirski subjekt - Žunkovič, Igor (Primerjalna književnost, 2014)
This article deals with the development of the lyric subject in the works of Gregor Strniša, one of the most important twentieth-century Slovenian poets. It starts by defining universal consciousness as an idea connected with the theory of relativity and quantum mechanics, and continues by determining various ways in which the idea of universal consciousness is articulated through Strniša's poetry. There is a development of the lyrical subject from one that articulates the idea of universal consciousness to one that seeks to describe the world from the viewpoint of universal consciousness.
Keywords: Strniša, Gregor, 1930-1987; Slovene literature; slovenska književnost; slovenska poezija; lirski subjekt; vesoljska zavest